Leitura literária na Educação Infantil: possibilidades e desafios na formação de leitores - Baião, Carolina de Paula (Universidade Federal do Tocantins, 2019)
In this research, we discuss the discussions regarding reading as an essential act for the life of the human being and in this perspective to investigate how this practice has been performed with small children, as well as general objective to analyze how the formation is being Of the reader, through the reading of literary works of the National School Library Program (PNBE 2012), in the class of Maternal II in a public school of Arraias-TO, in particular, read literature books for the children of this class; Seek information with the family and school about the reading practices of these children; Apprehend the perceptions of the families about literary reading; Stimulating families, students and teachers to be interested in the practice of literary reading; and analyze literary reading practices with and for children. For this, we conducted bibliographical studies with reference authors of the reading area and literary reading, such as Bicalho (2014), Coelho (2000), Cosson (2010, 2014, 2018), Cabral (1998), Cademartori (2010, 2014), Lima (2017), Martins (2003), Solé (1998) Silva (1993) Zilbermam (1991), Lajolo (2000), Paulino (2014), among others. For data collection, a qualitative approach was used using direct observations of the class of Maternal II were used. A proposed intervention was also carried out, consisting of reading stories for a class, twice a week. Each week, at the end of the reading, three children were chosen to take a book of history home that should be read and explored with family members. The analysis of the results demonstrated the need to invest and perform more and more literary readings in the lives of children in specific minors, in which it is not only a function of the school, but also of the families to promote activities of constant readings to The small ones, because they are in the two environments that spend most of the time.